Pemberdayaan Paguyuban UMKM di Kampung Wisata Kuliner Pring Koening Kota Malang - Rofieq, Mochammad; Siswati, Aris; Fauzy, Muchammad Riza (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
The empowerment of UMKM associations in the Pring Koening Culinary Tourism Village is one of the community service activities funded by the Ministry of Technology. There are 3 types of training activities and forums group discussion (FGD) carried out in this community empowerment. The first is training related to UMKM business management, the second is training related to digital marketing, and the third is training related to an entrepreneurial mindset for resilient UMKMs. It is hoped that these three training activities can improve the ability of UMKM  actors in the Pring Koening Culinary Tourism Village so that they can compete with other competitors. From the side of the service team, they also get an overview of the current conditions experienced by UMKM actors so that it can be a further study in the future. In addition, this activity also provides grants for several equipment needed by UMKMs there.